Moskva, Cheremushki op. 105 ; a musical comedy in three acts and five scenes ; [premier recording of the complete operetta] - Šostakovič, Dmitrij Dmitrievič 1906-1975 (Chandos Records, 1997)
Moskau - Cherimuschki: Operette in drei Akten und fünf Szenen. Libretto: V. Mass und M. Chervinski.
Interpr.: Baturkin, Andrej [Alexander Petrovich Bubentsov, Fyodor Mikhailovich Drebednyov]. Gelachova, Irina [Kurochkina, Masha, Mylkina, Vava, Nervous lady, Second lady construction worker]. Gujov, Michail [Semyon Semyonovich Baburov, A neighbour]. Prokina, Elena [Lidochka, Wife]. Ločak, Anatolij [Boris Koretsky]. Apajkin, German [Kurochkin, Mylkin, Sergey Glushkov, Husband, Man in a cap]. Chernykh, Lydia [Lyusya, A neighbour (f.), First lady construction worker]. Kisselev Alexander [Afanasi Ivanovich Barabashkin]. Rozhdestvensky, Gennady [Taxi driver, Conductor]. Russian State Symphonic Capella. Valeri Polyansky [Choreinstud.]. Residentie Orchestra The Hague. Roždestvenskij, Gennadij [Dir.]. - Russ. gesungen. - Aufn.: Dr Anton Philipszaal, The Hague, 30 June-3 July 1997. Premier recording of the complete operetta